Investigating the effect of government subsidies on enterprise research and development - Wu, Guangliang; Buravleva, Yana; Wu, Jing; Li, Yi; Tang, Decai; Bethel, Brandon J. (Frontiers in Environmental Science, 2022)
Governments design and implement policies to achieve a variety of goals, but perhaps none are as pressing as shifting national economies away from non-renewable fuels and towards more sustainable, environmentally-friendly technologies. To incentivize such transitions, governments provide subsidies to private and public companies to innovate, i.e., to engage in research and development (R&D). However, it can be asked if companies are using government subsidies (GS) to actually perform R&D, and the answer will determine the effectiveness of government policies. This paper seeks to answer this question through investigating Chinese lithium-ion battery (LiB) firms and the GS they receive. Hausman tests, fixed- and random-effects models confirmed a weak, though positive correlation between GS and R&D as determined by patent output (PO), but interestingly, observations of information flow suggested that GS also affected other variables such as net profit and main business income. This suggests that firms are being awarded GS for higher PO, but a corresponding increase in R&D and its expected growth in company performance is not occurring. It is suggested that performance indicators other than PO be used as Chinese firms may ab(use) this metric to apply for more GS, rather than performing R&D that leads to technological breakthroughs.